Analisis Kompetensi Penulisan Huruf Hijāiyah Tunggal Pada Siswa MIS UMMI Lubuk Pakam - Siti Mahrami Ivlatia; Nina Wandana; Dita Andini Harahap; Aslam Annashir; Sahkholid Nasution (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Mahārah kitābah is a skill in Arabic that requires skills and abilities to express ideas or all the contents of the mind in writing. In mahārah kitābah there are various problems in writing letters, including how to write Hijāiyah letters. This study aims to map students who are proficient in writing Hijāiyah letters and students who are less proficient in writing Hijāiyah letters, and find out what factors influence this. This research uses a qualitative-descriptive method. Data obtained through data were analyzed using 3 stages; Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of observations on 55 children of MIS UMMI Lubuk Pakam, as many as 53 children with a percentage of 96.3% in very good criteria. In the excellent criteria, it shows that children can write single Hijāiyah letters from ا to ي. A total of 2 children with a percentage of 3.6% in the moderate criteria. In the sufficient criteria, it shows that children can write single Hijāiyah letters but the Hijāiyah letters are incomplete according to the specified number.